Nursing and smoking doesn't go together - A qualitative investigation- assessing if a nurse's smoking status affects the delivery of smoking cessation advice to patients in the hospital setting - Machen, Samantha (2014)
Abstract Background In the last 20 years, interest into research around nurses who smoke has flourished, aiming to understand why nurses smoke given their unique position in healthcare and subsequent knowledge. Research has suggested that a nurse’s smoking status may be detrimental to smoking cessation efforts due to negative attitudes held by nurses who smoke. Negative attitudes include a lack of enthusiasm and a lack of belief that smoking cessation is not an effective treatment option. Aims of the Study & Methodology This study aimed to clarify the effect that a nurse’s smoking status may have upon SC efforts delivered in the hospital setting. To do this, six semi-structured interviews were carried out with staff nurses working in different specialties. The attitudes, beliefs and practices of the nurses were explored within the context of their smoking status to establish what impact their smoking status had upon their smoking cessation practice. The interviews were transcribed and analysed using thematic content analysis. Findings Nurses spoke positively of their role in providing smoking cessation to hospitalised patients, expressing that it was an important role and a role in which they believed they had the potential to be successful in. Unlike past research, negative attitudes around enthusiasm or lack of belief in the smoking cessation was not observed. No nurse expressed that their smoking status made them less likely to provide smoking cessation. The majority of the nurses reported that their smoking status meant they were in a better position to provide smoking cessation, as their experiences made the advice given appropriate, meaningful and in their eyes- effective. Future Research Future research should aim to explore if other smoking nurses view their smoking status positively in the context of providing smoking cessation and if so, why. Research should look to identify patient perspectives of receiving smoking cessation advice from a nurse who smokes.